Analysis of dynamics and opportunity cost of SME operations. (10th March 2023) - Bagodi, Virupaxi; Sinha, Deepankar
SMEs contribute significantly to the economy but have inconsistent growth and high mortality rates. Authors intend to comprehend the dynamics arising out of product-mix, markets, and governance affecting SME performance. Two hundred responses were obtained using a questionnaire. Cluster analysis was adopted for investigation. For each cluster, Bayesian-Pearson-correlation and Bayesian-linear-regression were carried out to determine the associations that were not explicit (frequentist approach). Results imply that a standard policy does not suit all SMEs and requires different prescriptions. Manufacturers of fixed type-of-products and those operating in the export-market show greater stability. Family businesses have slower growth rates but better customer-relations. Overtime and delay due to changes in production scheduling are two main ailments. None of the SMEs are lean and resilient. SMEs be categorised on their stage in the organisational life cycle, market it operates, ownership, type of product, supply-chain, and operations philosophy for better policy making.